A bacterial protein promotes the recognition of the Legionella pneumophila vacuole by autophagy. Issue 5 (8th April 2013) - Khweek, Arwa A.; Caution, Kyle; Akhter, Anwari; Abdulrahman, Basant A.; Tazi, Mia; Hassan, Hoda; Majumdar, Neal; Doran, Andrew; Guirado, Evelyn; Schlesinger, Larry S.; Shuman, Howard; Amer, Amal O.
<x xml:space="preserve">Abstract</x> Legionella pneumophila (L. pneumophila) is an intracellular bacterium of human alveolar macrophages that causes Legionnaires' disease. In contrast to humans, most inbred mouse strains are restrictive to L. pneumophila replication. We demonstrate that autophagy targets L. pneumophila vacuoles to lysosomes and that this process requires ubiquitination of L. pneumophila vacuoles and the subsequent binding of the autophagic adaptor p62/SQSTM1 to ubiquitinated vacuoles. The L. pneumophila legA9 encodes for an ankyrin‐containing protein with unknown role. We show that the legA9 mutant replicate in WT mice and their bone marrow‐derived macrophages. This is the first L. pneumophila mutant to be found to replicate in WT bone marrow‐derived macrophages other than the Fla mutant. Less legA9 mutant‐containing vacuoles acquired ubiquitin labeling and p62/SQSTM1 staining, evading autophagy uptake and avoiding lysosomal fusion. Thus, we describe a bacterial protein that targets the L. pneumophila‐containing vacuole for autophagy uptake.